1993
DOI: 10.1161/01.res.72.4.837
|View full text |Cite
|
Sign up to set email alerts
|

Physiological pH. Effects on posthypoxic proximal tubular injury.

Abstract: After O2 deprivation, tissue acidosis rapidly self-corrects. This study assessed the effect of this pH correction on the induction, and pathways, of posthypoxic proximal tubular injury. In addition, ways to prevent the resultant injury were explored. Isolated rat proximal tubular segments (PTSs) were subjected to hypoxia/reoxygenation (50/30 or 30/50 minutes) under the following incubation conditions: 1) continuous pH 7.4, 2) continuous pH 6.8, or 3) hypoxia at pH 6.8 and reoxygenation at pH 7.4 (NaHCO3 or Tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
44
0
2

Year Published

1993
1993
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 32 publications
0
44
0
2
Order By: Relevance
“…The PP-PLA2 additions were as follows: 20 Al of PP-PLA2 (P-6534, Sigma) was added to 230 Al of the incubation buffer, and then 25 Al of this dilution was added to the appropriate 2.5-ml PTS aliquots (final dilution, 1:1250, equivalent to 0.4 activity unit/ml; PLA2 activity as per Sigma). At completion of the 45-min incubations, cell injury was assessed by recalculating the percentage of LDH release, a well-recognized marker of hypoxic tubular cell death (9,(12)(13)(14)(15).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The PP-PLA2 additions were as follows: 20 Al of PP-PLA2 (P-6534, Sigma) was added to 230 Al of the incubation buffer, and then 25 Al of this dilution was added to the appropriate 2.5-ml PTS aliquots (final dilution, 1:1250, equivalent to 0.4 activity unit/ml; PLA2 activity as per Sigma). At completion of the 45-min incubations, cell injury was assessed by recalculating the percentage of LDH release, a well-recognized marker of hypoxic tubular cell death (9,(12)(13)(14)(15).…”
Section: Methodsmentioning
confidence: 99%
“…Male Sprague-Dawley rats (150-200 g; Charles River Breeding Laboratories), maintained under standard vivarium conditions, were used for all PTS isolations, done as described (13). In brief, after inducing anesthesia with pentobarbital (30-40 mg/kg), the kidneys were resected, minced, and partially digested with collagenase.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…During 1 h of anoxia, cell viability of freshly isolated PT cells de creased significantly to 54% ± 2% (P < 0.05), while no loss in viability was observed in cultured PT cells. Clamping the pH; during anoxia at 6.7 and 6.1 signifi-shown that acidification of hypoxic tissue, resulting from glycolytic lactate production, ATP hydrolysis and C 0 2 accumulation, can enhance the resistance to the damaging effects of O, deprivation in the kidney [7,24,[26][27][28][29], cardiomyocytes [3,16], and hepatocytes [10,11,13,18]. However, the mechanism behind the protec tion offered by lowering the pH is unknown.…”
Section: Introductionmentioning
confidence: 99%